Postmenopausal bleeding in a woman with caesarean scar defect: A case report - Hui Men Selina Chin; Zheng Yuan Ng; Liying Yang (Case Reports in Women's Health, 2020)
Background: Caesarean scar defect (CSD) is a complication of caesarean section with implications for abnormal uterine bleeding. Most cases of CSD are discovered incidentally or with the development of menstrual changes. However, CSD may rarely have a longer latency period, resulting in postmenopausal presentation of bleeding and abdominal pain. Case: A 52-year-old postmenopausal woman presented with acute suprapubic pain and postmenopausal bleeding. Pelvic ultrasonography and magnetic resonance imaging suggested bleeding from a CSD. Her symptoms resolved with expectant management. She subsequently underwent elective hysterectomy and bilateral salpingo-oophorectomy, which provided histological confirmation of a CSD. Conclusion: Caesarean scar defect should be considered in patients who present with acute abnormal uterine bleeding or pelvic pain with a history of caesarean section, even after menopause.